STEAM in Elementary School - Safran (International Conference on Elementary Education, 2025)
21st century education demands critical, creative, collaborative, and digital literacy skills. The STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach is an innovation that integrates various disciplines contextually to create meaningful learning. This study aims to analyze the application of STEAM in elementary schools by reviewing the supporting factors, constraints, and their impact on student learning processes and outcomes. The method used is a qualitative approach with library research, through the analysis of various research results, educational theories, and relevant policies. Data were obtained from secondary literature such as scientific journals, books, research reports, and purposively selected policy documents. Thematic content analysis was used to identify key themes such as teacher roles, facilities, policy support, and the impact of STEAM on learning outcomes. The results of the study show that the application of STEAM is efficacious in improving 21st century skills, including critical thinking, creativity, collaboration, and learning motivation. Project-based learning is the most effective strategy in integrating the five disciplines. However, the main obstacles include limited teacher competence, facilities, and policy support. Overall, STEAM has the potential to build creative and future-oriented basic education, noting the need for teacher training, adequate facilities, and interdisciplinary curriculum policies